Comparison of Percutaneous Transluminal Angiography With or Without Catheter-Directed Thrombolysis for Chronic Femoropopliteal Occlusive Disease. (29th March 2021) - Yi, Mengfei; Guo, Jianjun; Gao, Yanxia; Ren, Jianzhuang; Bi, Yonghua; Han, Xinwei
Background: Catheter-directed thrombolysis (CDT) is seldom used for chronic femoropopliteal occlusive disease. Methods: Patients with chronic femoropopliteal occlusive disease enrolled between January, 2011 and April, 2017. Hospitalization expense, limb salvage rate and survival rate were calculated. Results: Twenty-nine patients were treated with CDT (CDT group) and 31 patients without CDT (Non-CDT group).The mean hospitalization expense (5.2 ± 0.5), balloon catheter (1.0 ± 0.2) and stents number (0.8 ± 0.2) in CDT group were significantly less compared to Non-CDT group ( P < 0.05). The short-term and long-term effect scales showed similar in both groups. The incidences of perioperative complications (10.3% vs. 19.4%), primary patency and second patency rate, limb salvage rate (14.8% vs. 16.1%) and survival rate were also similar ( P > 0.05). Six patients died in each group and only 2 disease related deaths were found in Non-CDT group. Conclusion: CDT is a safe and economic strategy for patients with chronic femoropopliteal occlusive disease, and should be served as blanket treatment for every patient without thrombolytic contradictions or a remedy for failure PTA to achieve a comparable clinical effect.